CAR-T cells and CAR-Tregs targeting conventional type-1 dendritic cell suppress experimental autoimmune encephalomyelitis - Moorman, Cody D.; Yu, Sherman; Briseno, Carlos G.; Phee, Hyewon; Sahoo, Anupama; Ramrakhiani, Ambika; Chaudhry, Ashutosh (Frontiers in Immunology, 2023)
Conventional type 1 dendritic cells (DC1) contribute to the development of pathogenic T helper type 1 (Th1) cells in part via the production of the proinflammatory cytokine interleukin-12. Thus, depletion of DC1 has the potential to dampen autoimmune responses. Here we develop X-C motif chemokine receptor 1 (XCR1)-specific chimeric antigen receptor (CAR)-T cells and CAR-Tregs that specifically targeted DC1. XCR1 CAR-T cells were successfully generated as CD4+ and CD8+ T cells, expressed XCR1 CAR efficiently and induced XCR1-dependent activation, cytokine production and proliferation. XCR1 CAR-T cells selectively depleted DC1 when transferred into RAG2-/- mice with a compensatory increase in conventional type 2 DC (DC2) and plasmacytoid DC (pDC). XCR1 CAR-T cell mediated depletion of DC1 modestly suppressed the onset of Th1 driven experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. Diphtheria toxin-mediated DC1 depletion in XCR1-diphtheria toxin receptor mice also suppressed EAE, suggesting DC1 depletion was responsible for EAE suppression. XCR1 CAR-Tregs were successfully generated and suppressed effector T cells in the presence of XCR1+ cells. Therapeutic treatment with XCR1 CAR-Tregs suppressed Th1 driven EAE. Therefore, we conclude that depletion of DC1 with XCR1 CAR-T cells or immune suppression with XCR1 CAR-Tregs can modestly suppress Th1 driven EAE.